Keystone active bacterial lineages associated with Penaeus stylirostris shrimp health across larvae stages - Nolwenn Callac; Nelly Wabete; Carolane Giraud; Valérie Perez; Dominique Ansquer; Jean-Sébastien Lam; Dominique Pham; Viviane Boulo (PLoS ONE, 2025)
The Pacific blue shrimp, Penaeus stylirostris , reared in New Caledonia, is economically important for the territory. However, since 2005, this sector has been facing huge larval mortalities occurring at all larval stages in hatcheries and for which no causes have yet been found. Microbial dysbiosis of the larvae are suspected as factors leading to larval death. To test this hypothesis, we monitored daily the larval health based on their survival rate and developmental stage and explored the active microbiota of the larvae by sequencing the V4 region of the 16S rRNA sequence. Richness proxies exhibited lower values in the unhealthy (high mortality rate) larval microbiota compared to the healthy one, highlighting a loss of microbial diversity in the unhealthy larvae. Venn diagram comparisons displayed specific taxa associated with a given larval stage and health with several taxa being vertically transmitted among multiple larval stages of a same health status as shown in the core microbiota. Besides, at the zoea stage, when the mortalities started, three ASVs related to Tenacibaculum , Microscilla and Bernardetia were specific of the unhealthy zoea suggesting that the zoea stage is crucial for dysbiosis induction. It is therefore probably at this stage that dysbiosis of the microbiota could evolve into larval pathobiome and lead to larval death. Thus, identifying specific lineages related to dysbiosis, being specific or correlated to unhealthy larvae or to the pathobiome, and demonstrating their pathogenicity, could ultimately support larval rearing by enabling targeted responses to mitigate their impact.